Penerapan Geo-Spatial Business Intelligence dalam Analisis dan Visualisasi Survey Kondisi Jalan - Arsyad, Zulkifli; Umaroh, Sofia (Masoem University, 2024)
The road pavement condition survey aims to determine the Pavement Condition Index (PCI) value, which serves as the main indicator in determining road treatment strategies, such as routine maintenance, periodic maintenance, structural improvements, or reconstruction. In the manual execution of the road condition survey, the process involves walking along the road sections to be surveyed, taking samples from specific sections, which can take a relatively long time. In this study, an innovation was introduced to use video for recording road sections and performing analysis using an application. Data collection for the survey is carried out using video cameras with GPS technology mounted on vehicles to record road conditions in real-time. The telemetry data generated includes information on latitude, longitude, and vehicle speed, which is then further analyzed to create a dataset containing damage types, severity levels, damage dimensions, and other parameters. With the vast extent of provincial road sections reaching thousands of kilometers, Geospatial Business Intelligence (BI)-based street map technology is used to visualize and analyze survey results more effectively and quickly. The results of the study show that video and telemetry technology provide detailed information, while integration with Geospatial BI enhances the efficiency and speed of strategic decision-making related to road treatment.